2014
DOI: 10.1111/sbr.12077
|View full text |Cite
|
Sign up to set email alerts
|

Late bedtime is associated with decreased hippocampal volume in young healthy subjects

Abstract: Hippocampal volume loss has been described in several pathological conditions including sleep disorders. Whether differences in normal sleep are associated with differences in hippocampal volume is unknown. Here we designed a study to assess volume of the hippocampus with regard to bedtime, wake up time and sleep duration in 90 healthy university students. To assess hippocampal volumes we applied semi-automatic user-independent magnetic resonance volumetry. We found a significant association between delayed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This disturbance may eventually lead towards insomnia following the average score in sleep quality, by considering the symptoms such as difficulty in initiating sleep, awakening during sleep, not feeling well rested after sleep, daytime sleepiness and impaired functions [16], as experienced by the devices user. Indeed, it has been proven that the sleep quality is important in determining the hippocampus volume [17], however, was not conclusive to an increased risk of ganglio meningioma [18]. Moreover, our present study also showed that insomnia was not associated with illness in the past 6 months as reported by the respondents.…”
Section: Discussionsupporting
confidence: 44%
“…This disturbance may eventually lead towards insomnia following the average score in sleep quality, by considering the symptoms such as difficulty in initiating sleep, awakening during sleep, not feeling well rested after sleep, daytime sleepiness and impaired functions [16], as experienced by the devices user. Indeed, it has been proven that the sleep quality is important in determining the hippocampus volume [17], however, was not conclusive to an increased risk of ganglio meningioma [18]. Moreover, our present study also showed that insomnia was not associated with illness in the past 6 months as reported by the respondents.…”
Section: Discussionsupporting
confidence: 44%
“…Studies show that even one night of many nighttime wakings is associated with poorer performance on sustained attention and working memory tasks the next day [ 27 ]. Later sleep timing [which is more common among those experiencing daily stress; 28 ] may have associations with poorer memory performance, in part through covarying morphological changes in the hippocampus [ 29 ]. Thus, research suggests that multiple aspects of sleep [e.g., timing, duration, consistency, wakings/activity] should be considered, when examining sleep problems as they relate to stress and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with eveningness preference showed alterations in the structure and metabolism of a neural circuitry that was critical for accurate affective responses and emotional regulation ( Hasler et al., 2012 ; Kuperczkó et al., 2015 ; Rosenberg, Maximov, Reske, Grinberg, & Shah, 2014 ). As the relationship between eveningness and emotional dysregulation seems to be at least partly mediated by sleep complaints ( Levandovski et al., 2011 ; Rosenberg et al., 2014 ; Simor, Zavecz, et al., 2015 ), treatments focusing on circadian rhythms and sleep quality might be beneficial for patients with OCD.…”
Section: Discussionmentioning
confidence: 99%